Cultivating kharif onion under excess moisture stressed conditions - Ghodke, Pranjali H; Thangasamy, A; Mahajan, V; Gupta, A J; Singh, Major (Indian Horticulture, 2019)
Onion is one of the most widely grown and used vegetables in India with intrinsic export value. However, aberrant weather conditions namely heavy rainfall or excess soil moisture condition causes severe damage to onion crop and extensive economic losses to farmers. Heavy rainfall immediately followed by high temperature and humidity leads to serious losses in onion yield and quality. This damage is more pronounced in kharif onion production. Hence, a critical analysis of excessive rainfall in onion crop is essential to understand and develop the mitigation strategies so as to minimize the yield losses. This will definitely help the farmers to face such situations in future.